Ultra-stable nano-micro bubbles in a biocompatible medium for safe delivery of anti-cancer drugs - Bunyatova, Ulviye; Doğan, Mustafa; Tekin, Engincan; Ferhanoğlu, Onur (Springer Science and Business Media LLC, 2024)
AbstractWe conducted a series of experimental investigations to generate laser-stimulated millimeter bubbles (MBs) around silver nanoparticles (AgNPs) and thoroughly examined the mechanism of bubble formation within this nanocomposite system. One crucial aspect we explored was the lifetime and kinetics of these bubbles, given that bubbles generated by plasmonic nanoparticles are known to be transient with short durations. Surprisingly, our findings revealed that the achieved lifetime of these MBs extended beyond seven days. This impressive longevity far surpasses what has been reported in the existing literature. Further analysis of the experimental data uncovered a significant correlation between bubble volume and its lifetime. Smaller bubbles demonstrated longer lifetimes compared to larger ones, which provided valuable insights for future applications. The experimental results not only confirmed the validity of our model and simulations but also highlighted essential characteristics, including extended lifetime, matching absorption coefficients, adherence to physical boundary conditions, and agreement with simulated system parameters. Notably, we generated these MBs around functionalized AgNPs in a biocompatible nanocomposite medium by utilizing low-power light excitation. By readily binding potent cancer drugs to AgNPs through simple physical mixing, these medications can be securely encapsulated within bubbles and precisely guided to targeted locations within the human body. This capability to deliver drugs directly to the tumor site, while minimizing contact with healthy tissues, can lead to improved treatment outcomes and reduced side effects, significantly enhancing the quality of life for cancer patients.
Keywords: Composite material; Parallel computing; Bubble modeling; Silver; Science; Health Status; Materials Science; Biomedical Engineering; Metal Nanoparticles; Antineoplastic Agents; Photosensitive bio-nanocomposite; Ultra-stable sub-millimeter bubbles AgNPs colloidal; FOS: Medical engineering; Article; Biomaterials; Low laser excitation; Engineering; Nanoparticle; Applications of Ultrasound in Nanostructured Materials Synthesis; Acoustic Bubbles; Materials Chemistry; Humans; Nanotechnology; Bubble; Multi-layered structure; FOS: Nanotechnology; Nanocomposite; Biocompatible material; Computer science; Materials science; Absorption (acoustics); Laser Ablation Synthesis of Nanoparticles; Nanoparticle-Based Drug Delivery Systems; Physical Sciences; Quality of Life; Medicine; Biomedical engineering